Excessive Alcohol Intake and Health Outcomes Nexus among Youths in Mushin Area of Lagos State, Southwest Nigeria (African Journal of Biomedical Research, 2024)
Excessive alcohol intake is apparent among youths in Nigeria, and its perceived health implications among this population is lacking. Therefore, this study seeks to explore the prevalence and health implications of excessive alcohol intake among Mushin youths residing in Itire suburbs of Mushin local government area (LGA) of Lagos State, Nigeria. The study design adopted was descriptive cross-sectional, conducted in the district area of Mushin local government area in Lagos State, Southwest geopolitical zone of Nigeria. Using a systematic sampling technique, a final sample of 400 youths was selected for the study. Data on the outcomes of interest were gathered between August and November 2022 using an interviewer-administered structured survey questionnaire. The data were analyzed using descriptive and inferential statistics. Findings revealed that 89.0% of the respondents were alcohol abusers and 89.5% of them mentioned enjoyment as one of the main reasons for their drinking behaviours. The multiple linear regression analysis showed that factors such as ‘significant others’ (t = 6.892, ρ < 0.05), price of alcohol (t = 6.392, ρ < 0.05), and males more prone (t = 3.134, ρ < 0.05), significantly predicted a higher likelihood of excessive intake of alcohol. However, peer pressure (t = -3.869, ρ < 0.05) and age cohorts’ acceptance (t = -5.080, ρ < 0.05) were statistically significant, characterized by a negation of denial of respondents predicting the odds of excessive alcohol intake and its health implications. Thus, there is urgent need to create awareness programmes that will sensitize Mushin youths of the health consequences of excessive alcohol intake, especially in rural and grassroots communities in Nigeria.